Il Martyrion di Hierapolis di Frigia (Turchia) : Analisi archeologica e architettonica - Gümgüm, Güven (BAR International Series, 2012)
"Hierapolis (Phrygia) is located in Turkey in the territory of Pamukkale-Denizli. The city was known in antiquity for the cult of Cyble, patron goddess of the colony since its foundation. Hierapolis experienced a period of extraordinary prosperity both economically and politically throughout the 2nd century A.D. and into the early years of the 3rd century A.D., corresponding to the phase of monumentalization of the city. On the hill overlooking the east of the city is an imposing octagonal building, built in the late 4th and early 5th centuries A.D, erected as a 'martyrion' in honour of Saint Philip. Among other key monuments of this important ancient city, this study concentrates on the martyrion with the main objective of increasing knowledge of the building from an architectural point of view and aimed at retrieving a data set useful for planning a future restoration project. In addition, an aim of the research was to contribute to the knowledge of religious architecture between the 4th and 6th centuries in Asia Minor within the field of the history of late antique architecture. Most of the work was dedicated to the realization of plans and prospects which have allowed detailed analysis of each part of the building. It is hoped this work on the topographical-historical framework of Hierapolis will contribute to the study of similar architectural structures by presenting a seriation of masonry structures and technical solutions applicable also to other regions." -- Publisher's web site.